The internal and external factors that determined private investment in Ecuador 2007-2020 - Guido Macas-Acosta; Genesis Macas-Lituma; Arnaldo Vergara-Romero (Economies, 2022)
This article studies how electoral processes and internal factors of the Ecuadorian economy affect the dynamics of the country's business expectations. The hypothesis that the free market and socialist political models in an economy generate different reactions in the expectations of the agents, according to the prevailing macroeconomic context, is tested. The empirical analysis is based on time series tools on quarterly data between 2006 and 2021. The results show that the dynamics of investment adjustment to the relationships of internal factors, electoral processes, and other variables explain 84% of this behavior. This is more accelerated in political contexts that promote the free market and maintain social, political, and economic stability, showing an overreaction of agents to negative economic news following the loss-aversion hypothesis.
Keywords: 330; electoral processes; loss-aversion hypothesis; private investment; time series